Encapsulation of Lead Sulphide in SBA-15 Molecular Sieve - Zhai, Qing-Zhou; Xu, Zhi-Kun; Xue, Yu (Asian Journal of Chemistry, 2010)
The nanosized channels of SBA-15 molecular sieve were used as template and nanosized lead sulfide was prepared inside them. Pb2+ was firstly incorporated into the SBA-15 by ionexchange method, then the nanosized PbS was prepared in the channels of the SBA-15 molecular sieve using thioacetamide as sulfur source. The (SBA-15)-PbS composite materials were characterized by chemical analysis, powder X-ray diffraction, Fourier transform infrared spectroscopy, low-temperature nitrogen adsorption-desorption technique at 77 K, solid state diffuse reflection absorption spectroscopy and luminescence studies. The PbS has been successfully incorporated in the channels of the SBA-15 molecular sieve and the framework of the SBA-15 in the prepared composite material was kept intact. The prepared host-guest composite material presents luminescence performance and the materials may be hopefully applied to the field of optical materials.